Catholics, evangelicals and human rights: a study on their differences in chilean secondary school students - Núñez Hernández, Rodolfo; Ramírez Venegas, Cecilia; Sanhueza Vidal, Krety; Quezada Maya, Nilda (Última Década, 2019)
This research examines the relation between religion and Human Rights in Chilean Catholic and Evangelical secondary school students. The theoretical schemata about the construction of values and their relation with the appreciation of certain human rights, describe the acquisition of behavioral patterns that remain through time as a result of the involvement of agencies of socialization such as family and school. The religious ethos of these Christian students, measured in this quantitative research through correlation and multiple regression analysis, shows minimal differences between Catholics and Evangelicals in their value base; their position is significantly contrary towards euthanasia and death penalty, and significantly supportive towards the regulation of external institutions such as the State, concerning to the practice of sexuality in private contexts. Differences between Catholics and Evangelicals can be still evidenced, nevertheless, by the theoretical aspects of both religions in Chile, their minority or majority condition in the context of the school, as an agency of socialization, and “political anomie”. As Christians, in their differentiation between Catholics and Evangelicals, drift away from their practice and commitment with their own religion, answers will become either less significant or completely opposite.